Bivalent single-domain antibodies show potent mpox virus neutralization through M1R antigen - Akazawa, Daisuke; Shimojima, Masayuki; Park, Eun-Sil; Okutani, Akiko; Virhuez-Mendoza, Milagros; Inoue, Yusuke; Hishiki, Takayuki; Maeda, Ken; Ebihara, Hideki; Takahashi, Yoshimasa; Watashi, Koichi (Communications biology, 2025)
Despite the recent mpox outbreak raising global concerns, no fully validated antiviral treatment exists, highlighting the urgent need for effective therapeutics. Here, by taking advantage of the preparation technology for single-domain (VHH) antibodies, we generated VHHs targeting the six major mpox virus (MPXV) surface antigens. Although neutralization activity of these monoclonal VHH monomers was negligible, bivalent VHHs against MPXV-M1R (bi-M1A8 and bi-M1C2) improved the antigen binding affinity by up to over 400-fold compared with the monomer VHH and thus produced neutralizing activity against MPXV. Epitope analysis by SPR revealed that the two neutralizing bivalent VHHs recognized different epitopes within M1R antigen. Importantly, these bivalent VHHs were active to multiple MPXV clades and related cowpox virus. We also showed the effect of bi-M1A8 on reducing the MPXV DNA and infectious titer in an MPXV infection mouse model. These VHH modification approaches provide a new strategy for anti-MPXV drug development. This study demonstrates that multimerization of single-domain antibodies (VHHs) targeting MPXV M1R significantly enhances neutralizing activity. the approach offers a modular platform for engineering next-generation antivirals against orthopoxviruses.